Transcriptomic and physiological responses of Skeletonema costatum to ATP utilization. (22nd February 2020) - Zhang, Xiaohua; Lin, Senjie; Liu, Dongyan
Summary: The capacity of phytoplankton to utilize dissolved organic phosphorus (DOP) plays an important role in their competition for resources when the availability of dissolved inorganic phosphorus (DIP) is low in the aquatic systems. Here, we explored the physiological and molecular responses of a globally distributed marine diatom, Skeletonema costatum, in utilizing adenosine‐5′‐triphosphate (ATP) based on incubation experiments under ATP, DIP‐replete, and DIP‐depleted conditions. The results show that ATP supports the growth of S. costatum as efficiently as DIP. The pathway of S. costatum involved in utilizing ATP is not related to alkaline phosphatase (AP), an important DOP hydrolase, although extracellular hydrolysis is involved. The transcriptome analysis revealed several transcripts related to the hydrolase activity (e.g. NAD+ diphosphatase), which were significantly upregulated in the ATP culture group, indicating their possible involvement in ATP hydrolysis. Meanwhile, ATP‐grown S. costatum exhibited downregulation of the genes related to a series of metabolic activities (e.g. purine metabolism), apparently to adapt to ATP condition.